The Journey of Becoming a Hero in the Avatar: The Last Airbender Animated Series - Cindy Karina; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
The popularity of Avatar: The Last Airbender intrigues me to analyze Aang’s journey, as the main character, in becoming a hero. I aim to analyze the stressors that cause Aang’s psychological distress, his coping mechanisms, and how he develops into a hero. To find out about the three aforementioned points, I use theories on psychological distress and coping mechanisms. My analysis demonstrates that Aang’s psychological distress is caused by three stressors: his fear of accepting his new identity and responsibility, his shame, and his fear of the war and failure. To deal with those stressors, Aang adopts two coping mechanisms: emotion-focused (avoidance, seeking social support for emotional purposes, and acceptance), and problem-focused (seeking social support for instrumental purposes, planning, and problem-solving). By the end of the series, Aang has become a hero by developing into a selfless and benevolent humanitarian who used his intelligence and integrity to win the war.Keywords: psychological distress, stressors, coping mechanism, hero